Early life microbial exposure, child neurocognition and behaviour at 2 years of age: A birth cohort study. (29th November 2019) - Senn, Elizabeth; Symeonides, Christos; Vuillermin, Peter; Ponsonby, Anne‐Louise; ,
Abstract : Aim: To investigate the relationship between factors which influence external microbial exposures (FEMEs), previously identified to be protective or to increase the risk of the development of allergic disease, and cognition and behaviour in infants 2 years of age in an Australian population. Method: The Barwon Infant Study is a birth cohort ( n = 1074) in Victoria, Australia. Comprehensive questionnaire, clinical and biological measures were collected at multiple time oints. Multiple linear regression was used to evaluate the associations between 56 FEMEs and 3 outcomes; cognition (Bayley Scales of Infant and Toddler Development (BAYLEY‐III)) ( n = 667, mean (standard deviation) age = 2.45 (0.14) years), internalising and externalising behaviour (Child Behavior Checklist) ( n = 666, mean (standard deviation) age = 2.45 (0.14) years). Results: Overall, there were no consistent patterns or dose response found within an outcome nor across all three outcomes, although there was some evidence for individual associations. Breastfeeding and child care were associated with higher cognitive scores (adjusted mean difference (95% confidence interval) = 3.20 (0.23–6.17) and 0.68 (0.12–1.24), respectively), and increasing sibling number was associated with lower internalising behaviour (adjusted mean difference (95% confidence interval) = −4.13 (−6.34, −1.91)). Conclusion: In contrast to allergic disease, there was an absence of epidemiological evidence to support the association between these FEMEs and cognition and behaviour. Direct investigations into the relationship between exposures which influence gut‐microbial composition and cognition and behaviour are now needed.